Resiliensi Komunitas Mahasiswa Eks-Hizbut Tahrir Indonesia di Universitas Islam Negeri Sunan Ampel Surabaya Pasca-Perppu Nomor 2 Tahun 2017 - Novita, Almi; Al-Amin, Ainur Rofiq; Umam, Muchammad Helmi (FIKRAH, 2020)
Hizbut Tahrir Indonesia (HTI) was officially disbanded in 2017 by the government accordance with Perppuu No.2 of 2017. The ex-Hizbut Tahrir Indonesia (HTI) did not immediately dissolve their movement, but more massive preaching of Islamic law within the framework of the caliphate in various regions especially on campus. The ex-Hizbut Tahrir Indonesia continue to recruit members by conducting various routine studies of Islam, such as the MALKIS study (Study of Exist Sunday Night) which is routinely carried out by the ex-Hizbut Tahrir Indonesia student community at UIN Sunan Ampel Surabaya. The purpose of this research to know and analyze the development and resilience of the ex-Hizbut Tahrir Indonesia student community after was disbanded in the UIN Sunan Ampel campus. This article uses descriptive qualitative research methods to present data and reveal events or facts. The results showed that the resilience of the ex-Hizbut Tahrir Indonesia (HTI) student community at UIN Sunan Ampel Surabaya could rise and come out of a stressful after was disbanded.